Detecção molecular do bocavírus felino (FBoV) e parvovírus felino (FPV) em gatos filhotes com diarreia - Almeida, Julio Cesar Neves de (2023)
Feline bocavirus (FBoV) and Carnivore protoparvovirus-1 (CPPV-1) are non-enveloped, linear single-stranded DNA viruses that belong to the Parvoviridae family and, these viruses are a potential cause of enteropathies in cats. Feline bocavirus was poorly evaluated with respect to its occurance in the world. Although feline parvovirus has a reemerging character due to recent reports of outbreaks in several countries. Thus, the aim of the study was to evaluate the occurrence and the genetic characterization of FBoV and CPPV-1 in cats with less than one year old and clinical manifestation of diarrhea. The study included a sampling of 75 cats to be investigated for the presence of FBoV and 85 cats for CPPV-1. The kittens were separated into two groups: Group 1 (G1), which consisted of diarrheal kittens from different origins, sampled at domiciles, veterinary hospitals or clinics; and Group 2 (G2), which consisted of diarrheic group-housed kittens or from to the same shelters. Fecal samples were collected using rectal swabs or flexible urethral catheters for rectal samples. Subsequently the clarification and extraction of DNA from the samples were performed. The extraction product was subjected to PCR targeting the bacterial 16S rRNA gene andthe NP1 gene region for the FBoV screening, and to qPCR targeting the VP2 gene region for CPPV-1 detection. FBoV was detected in 17,8% (13/73), 12,8% (5/39) of the cats belonging to G1 and 23,5% (8/34) to G2. Seven samples of the 13 were sequenced, 42,8% (3/7) were classified as FBoV-1, 28,5% (2/7) as FBoV-2 and 28,5% (2/7) as FBoV-1 and FBoV-3 simultaneously. Positive samples were submitted to complete sequencing of the variant VP2 gene to determine the CPPV-1 and to the partial sequencing of the NS1 gene for FBoV genotyping. As a result, two samples were negative in the internal control, one in each group. CPPV-1 was detected in 43,4% (36/83) samples, with 40,9% (18/44) of the cats belonging to G1 and 46,1% (18/39) to G2. Four CPPV-1-positive samples and one FPV vaccine were sequenced, three of the samples were classified as feline parvovirus and one as canine parvovirus. This study provides data on the occurrence of FBoV and CPPV-1 in kittens with diarrhea. It highlighted the presence of feline and canine variants of CPPV-1, in addition to the first molecular evidence of the presence of FBoV in cats in Brazil, with proof of the circulation of the three known species (FBoV-1, 2 and 3).